Introduction of Asian canine parvovirus in Europe through dog importation. Issue 1 (13th November 2017) - Mira, F.; Purpari, G.; Lorusso, E.; Di Bella, S.; Gucciardi, F.; Desario, C.; Macaluso, G.; Decaro, N.; Guercio, A.
Summary: Canine parvovirus (CPV) is an important infectious agent of domestic and wild carnivores, responsible for severe and often fatal haemorrhagic gastroenteritis and leukopenia. This paper reports the genomic characterization of a CPV strain collected from a dog recently imported to Italy from Thailand. The virus was detected in all tissue samples collected. The whole genome encompassing the two open reading frames encoding for non‐structural (NS1/NS2) and structural (VP1/VP2) proteins was amplified and sequenced. On the basis of genetic analysis of the VP2 gene, the isolate was characterized as CPV‐2c, but it presented genetic signatures typical of Asian strains. Sequence analysis revealed the presence of amino acid changes never observed in European CPV‐2c strains (NS1: Ile60Val, Tyr544Phe, Glu545Val, Leu630Pro; VP2: Ala5Gly, Phe267Tyr, Tyr324Ile, Gln370Arg). By phylogenetic analysis of full‐length VP2 gene, the analysed strain clustered together with Asian viruses. Therefore, a possible introduction of the virus from Asia through the imported dog was suggested, thus confirming the important role of movement of dogs in the global spread of viruses. In addition, full‐length genome analysis could help better trace the spread of canine viruses through different continents.